Adjuvant EGFR-TKI therapy in resected EGFR-mutation positive non-small cell lung cancer: A real-world study - Liu, Jun-Feng; Sun, Xu-Sheng; Yin, Jin-Huan; Xu, Xi-E (Frontiers in Oncology, 2023)
Background: Although several clinical studies have laid the foundation for the adjuvant application of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), some questions remain unresolved. This real-world study aimed to address questions such as the effect of adjuvant chemotherapy prior to adjuvant EGFR-TKI therapy on survival outcomes, and the duration of adjuvant EGFR-TKI therapy, etc. Methods: Between October 2005 and October 2020, 227 consecutive patients with non-small cell lung cancer (NSCLC) who underwent complete pulmonary resections were included in this retrospective study. Patients received postoperative adjuvant chemotherapy followed by EGFR-TKI or adjuvant EGFR-TKI monotherapy. The disease-free survival (DFS) and overall survival (OS) were evaluated. Results: Of the total 227 patients, 55 (24.2%) patients underwent 3-4 cycles of chemotherapy prior to receiving adjuvant EGFR-TKI therapy. The 5-year DFS rate was 67.8%, while the 5-year OS rate was 76.4%. The stages were significantly associated with both DFS (P<0.001) and OS (P<0.001), while no significant differences were observed in the DFS (P=0.093) and OS (P=0.399) between the adjuvant chemotherapy followed by EGFR-TKI and adjuvant EGFR-TKI monotherapy groups. A longer duration of EGFR-TKI therapy was associated with better DFS (P<0.001) and OS (P<0.001) benefit. Additionally, pTNM stage and duration of EGFR-TKI therapy were considered independent prognostic factors for long-term survival (All P<0.05). Conclusions: This study supports the use of EGFR-TKI as a postoperative adjuvant treatment for patients with stage II-IIIA EGFR-mutation positive NSCLC. Additionally, patients with stage I who had pathological risk factors were also suitable for receiving adjuvant EGFR-TKI therapy. Postoperative EGFR-TKI based, chemotherapy-free adjuvant regimen may be a potential therapeutic option for patients with EGFR-mutation positive NSCLC.